KCNJ5 Somatic Mutation Is Associated With Higher Aortic Wall Thickness and Less Calcification in Patients With Aldosterone-Producing Adenoma - Lee, Bo-Ching; Kang, Victor Jing-Wei; Pan, Chien-Ting; Huang, Jia-Zheng; Lin, Yu-Li; Chang, Yi-Yao; Tsai, Cheng-Hsuan; Chou, Chia-Hung; Chen, Zheng-Wei; Liao, Che-Wei; Chiu, Yu-Wei; Wu, Vin-Cent; et al. (Frontiers in Endocrinology, 2022)
Objective Primary aldosteronism (PA) is the most common type of secondary hypertension, and it is associated with a higher rate of cardiovascular complications. KCNJ5 somatic mutations have recently been identified in aldosterone-producing adenoma (APA), however their influence on vascular remodeling and injury is still unclear. The aim of this study was to investigate the association between KCNJ5 somatic mutation status and vascular status. Methods We enrolled 179 APA patients who had undergone adrenalectomy from a prospectively maintained database, of whom 99 had KCNJ5 somatic mutations. Preoperative clinical, biochemical and imaging data of abdominal CT, including abdominal aortic calcification (AAC) score, aortic diameter and wall thickness at levels of superior (SMA) and inferior (IMA) mesenteric arteries were analyzed. Results After propensity score matching for age, sex, body mass index, triglycerides and low-density lipoprotein, there were 48 patients in each KCNJ5 (+) and KCNJ5 (-) group. Mutation carriers had a lower AAC score (217.3±562.2 vs. 605.6±1359.1, P=0.018), higher aortic wall thickness (SMA level: 2.2±0.6 mm vs. 1.8±0.6 mm, P=0.006; IMA level: 2.4±0.6 mm vs. 1.8±0.7 mm, P<0.001) than non-carriers. In multivariate analysis, KCNJ5 mutations were independently associated with AAC score (P=0.014) and aortic wall thickness (SMA level: P<0.001; IMA level: P=0.004). After adrenalectomy, mutation carriers had less aortic wall thickness progression than non-carriers (thickness SMA: -0.1±0.8 mm vs. 0.9±0.6 mm, P=0.024; IMA: -0.1±0.6 mm vs. 0.8±0.7 mm, P=0.04). Conclusion KCNJ5 mutation carriers had less calcification burden of the aorta, thickened aortic wall, and less wall thickness progression than non-carriers.